Research on resource monitoring and billing mechanisms of application engine in cloud computing environment - Yi REN; Jing ZHANG; Hong CHEN; Qing-bo WU; Jin-zhu KONG; Hua-dong DAI; Gang GUAN (Tongxin xuebao)
A comprehensive study on the billing methods of existing cloud computing platforms was made.Then,AppScale,an open sourced scalable and typical PaaS software,as the foundation platform of our target resource monitoring and billing mechanisms was chose.Appscale’s structure,its components and how they worked together was analyzed.CloudMB,which enhanced AppScale by supporting process level resource monitoring and multi-user oriented billing function with flexible billing policies was designed and implemented.Finally,experiment verified that CloudMB is effective and its occupation of CPU time is lower than 3%.